Pain Management for Infants during Vaccination: Evaluation of Online Resources and Pilot Testing of Parent-Targeted Interventions - Modanloo, Shokoufeh (Université d'Ottawa / University of Ottawa, 2020)
The overall aim of this thesis was to improve the use of recommended pain management strategies during infant vaccination by investigating the quality and use of evidence-based online parent resources. Study 1: A two-armed pilot randomized control trial (RCT) was conducted to evaluate the feasibility, acceptability and preliminary efficacy of two interventions, delivered online, aimed at improving the use of recommended pain management strategies during infant vaccination. Parents of infants < six months old were randomized to 1) Be Sweet to Babies videos and tip sheet; and 2) Be Sweet to Babies videos, tip sheet and Motivational Interviewing-informed Affirmative Statements and Questions (AS&Q). Results showed it was feasible to recruit parents via online means (201 eligible respondents recruited in a week, 170, 85% provided written consent, and 89, 59% completed all data collection. From these 89 participants, there was high acceptability of the study, 84 (94%) were satisfied with study processes, and 78 (88%) intended to recommend the strategies to others. For preliminary efficacy, almost all participants used at least one of the pain management strategies in the subsequent vaccination (Intervention 1 (49, 98%); Intervention 2 (38, 95%)). There were no significant differences in the use of pain management strategies between the two study groups. Study 2: To investigate the quality of online parent resources about vaccination pain management, an environmental scan of Google and Social Media networks (i.e. Facebook, YouTube, and Twitter) was conducted. The quality of resources was evaluated using the Center for Diseases Control and Prevention (CDC) Clear Communication Index. 65 resources (55 written, 10 videos), were included. The mean quality score was 60% ± 0.19. Only 5% of resources scored an acceptable quality of >90%. Only 30 (46%) resources included evidence-based content on pain management strategies during vaccination, which included breastfeeding (24, 37%), holding (27, 42%), and sweet solutions (22, 34%). Most publicly accessible online parent-targeted vaccination resources were of poor to moderate quality and did not contain pain management information during vaccination. The study was shown to be feasible and acceptable to those parents who completed the study. The Internet is an efficient way to recruit parents for trial participation and to disseminate knowledge.
Keywords: Childhood vaccination; Pain management; Parents; Knowledge translation